[Man-Induced Geyser] - Streng, Evelyn Fiedler (1975)
Photograph of a man-induced geyser. The white, exploding geyser sits at the center of the photograph, protruding from black rocks along the bottom of the photograph. White buildings with red roofs cover the hills in the background below a tall, grey and green mountains. The photograph is blurry.